2011
DOI: 10.1371/journal.pone.0019493
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Dissemination of SIV Follows Multisite Entry after Rectal Inoculation

Abstract: Receptive ano-rectal intercourse is a major cause of HIV infection in men having sex with men and in heterosexuals. Current knowledge of the mechanisms of entry and dissemination during HIV rectal transmission is scarce and does not allow the development of preventive strategies. We investigated the early steps of rectal infection in rhesus macaques inoculated with the pathogenic isolate SIVmac251 and necropsied four hours to nine days later. All macaques were positive for SIV. Control macaques inoculated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
46
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 85 publications
3
46
0
Order By: Relevance
“…Risk factors pertaining to MSM include anal intercourse [2], differences in transmission route and kinetics of viral dissemination [3], and inadequate access to preventative health care services [4-7]. Thus, MSM remain among the populations most highly affected by HIV-1 in both resource–rich and –poor settings [8].…”
mentioning
confidence: 99%
“…Risk factors pertaining to MSM include anal intercourse [2], differences in transmission route and kinetics of viral dissemination [3], and inadequate access to preventative health care services [4-7]. Thus, MSM remain among the populations most highly affected by HIV-1 in both resource–rich and –poor settings [8].…”
mentioning
confidence: 99%
“…The single-layer columnar epithelium of the rectum differs from the multilayered squamous epithelium that covers the vagina and has a unique immunological composition and CCR5 distribution that may influence early establishment and dissemination of infection (14)(15)(16)(17). In humans, MVC exposure after oral dosing also differs in rectal and vaginal tissues, likely due to differences in tissue vascularization, drug trapping in mucus, and protein binding (7,8).…”
mentioning
confidence: 99%
“…In GALT, virus can be detected in T cells, DC-SIGN+ cells, and other unknown subsets at this early stage (Ribeiro Dos Santos et al, 2011). However, we and others (Xu et al, 2013c) have shown that SIV infection downregulates CD3, CD4, and likely many other molecules in vivo ( Figure 3); thus, definitively determining target cell subsets in tissues remains a challenge.…”
Section: Rectal Siv Transmissionmentioning
confidence: 84%